Rekonstruksi Hermeneutika Sunnah:: Distingsi Sunnah Rasūliyyah dan Sunnah Nabawiyyah Muhammad Syahrur - Prayoga, Dedi (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2025)
The position and authority of the Sunnah continue to be reconstructed in response to the development of modern hermeneutical approaches to religious texts. One of the most influential contemporary Muslim thinkers addressing this issue is Muhammad Syahrur, who proposes a new conceptual framework for understanding the Sunnah through linguistic-semantic and historical-contextual analysis. This study examines Syahrur’s distinction between Sunnah al-Rasūliyyah and Sunnah al-Nabawiyyah as a response to the epistemological problem of hadith authority and the demands of modern ijtihad. The research employs a qualitative library-based method, using Syahrur’s major works Al-Sunnah al-Rasūliyyah wa al-Sunnah al-Nabawiyyah, Al-Kitāb wa al-Qur’ān, and Nahwa Uṣūl Jadīdah li al-Fiqh al-Islāmī as primary sources. Data are analyzed through descriptive-analytical and hermeneutical approaches, focusing on conceptual mapping, semantic examination, and historical contextualization. The findings demonstrate that Syahrur categorizes Sunnah al-Rasūliyyah as a normative, universal, and binding dimension of prophetic guidance, while Sunnah al-Nabawiyyah is understood as historically contingent prophetic practices that are not universally binding. This distinction provides a methodological basis for the contextual reinterpretation of the Sunnah and contributes significantly to contemporary Islamic legal epistemology by offering a more adaptive model of understanding prophetic authority in changing socio-historical contexts.